Overall Quality of Outcomes Framework scores lower in practices in deprived areas - Wright, Jim (Oxford University Press, 2006)
BACKGROUND: There has been much debate as to whether quality points allocated through the new general medical services contract are more difficult to achieve for practices in deprived and rural areas. We used multiple regression to assess the relationships between deprivation, rurality and the number of overall quality points achieved by each practice. Multiple deprivation was significantly inversely related to quality points achieved. Practices in villages and towns gained 2% more quality points than urban areas and hamlets.